2004
DOI: 10.1128/aem.70.10.6347-6351.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Identification of a Putative Vinyl Chloride Reductase in Dehalococcoides sp. Strain BAV1

Abstract: Dehalococcoides sp. strain BAV1 couples growth with the reductive dechlorination of vinyl chloride (VC) to ethene. Degenerate primers targeting conserved regions in reductive dehalogenase (RDase) genes were designed and used to PCR amplify putative RDase genes from strain BAV1. Seven unique RDase gene fragments were identified. Transcription analysis of VC-grown BAV1 cultures suggested that bvcA was involved in VC reductive dechlorination, and the complete sequence of bvcA was obtained. bvcA was absent in Deha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
240
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(248 citation statements)
references
References 40 publications
4
240
0
4
Order By: Relevance
“…All these 32 rdhAB pairs share numerous characteristics with the biochemically characterized trichloroethene reductive dehalogenase of strain 195 (tceA) 14 , the vinyl chloride reductive dehalogenase of Dehalococcoides sp. strain BAV1 15 , a vinyl chloride reductive dehalogenase isolated from Dehalococcoides sp. strain VS in highly enriched culture 16 and rdh loci in other bacteria growing by respiratory dehalogenation.…”
Section: Comparison With D Ethenogenes Strain 195mentioning
confidence: 99%
“…All these 32 rdhAB pairs share numerous characteristics with the biochemically characterized trichloroethene reductive dehalogenase of strain 195 (tceA) 14 , the vinyl chloride reductive dehalogenase of Dehalococcoides sp. strain BAV1 15 , a vinyl chloride reductive dehalogenase isolated from Dehalococcoides sp. strain VS in highly enriched culture 16 and rdh loci in other bacteria growing by respiratory dehalogenation.…”
Section: Comparison With D Ethenogenes Strain 195mentioning
confidence: 99%
“…Furthermore, assessing the presence of genes that encode for VC reductive dehalogenases (rdhA) known to catalyze VC reduction to ethene, such as vcrA, and measuring genes' mRNA level constitutes a stronger line of evidence to support complete reductive dechlorination. The vcrA and bvcA genes identified in Dhc are so far the only two functional genes described to encode VC rdhA (Krajmalnik-Brown et al, 2004;Müller et al, 2004) and their presence in field samples from sites contaminated with chlorinated ethenes was successfully related to complete dechlorination (Scheutz et al, 2008;van der Zaan et al, 2010;Damgaard et al, 2013a). It was moreover shown based on field samples that rdhA genes directly involved in dechlorination should be targeted in addition to Dhc, as different microbial species might harbour vcrA and bvcA genes due to horizontal gene transfer and are therefore also able to dechlorinate VC down to ethene (van der Zaan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several molecular tools have been developed for examining a broad range of rdhA genes in a given sample (site, isolate or mixed culture), including both microarray-based methods and PCR-based protocols [60][61][62][63]. Identification of novel reductive dehalogenase genes has primarily come from PCR studies [32,33,[35][36][37]39,40,42] and subsequently from genome and metagenome sequencing efforts [6,13,14,41,63], with each new organism or environment sampled increasing the known diversity of putative rdhA genes.…”
Section: Reductive Dehalogenasesmentioning
confidence: 99%
“…The first gene sequences encoding reductive dehalogenases were identified using classical reverse genetics approaches based on partial amino acid sequences of purified enzymes [30,31]. PCR and genome studies have since identified new sequences with high sequence identity to the characterized genes [6,13,14,[32][33][34][35][36][37][38][39][40][41][42]. Reductive dehalogenase genes (or reductive dehalogenase homologous genes (rdh) if the encoded protein has not yet been biochemically characterized) typically comprise an operon containing rdhA, the gene for the catalytically active enzyme (RDase if characterized, otherwise RdhA), rdhB, a gene encoding a putative membrane-anchoring protein [34], and sometimes one or more members of rdhTKZECD, genes associated with reductive dehalogenase genes [43].…”
Section: Reductive Dehalogenasesmentioning
confidence: 99%